Choosing schools, choosing (adult) friendships: National language, progressive self-fashioning, and social envy among Brazilian and Puerto Rican elites - Ana Y. Ramos-Zayas (economic sociology. perspectives and conversations, 2023)
Drawing from extensive ethnographic research among upper-class parents affiliated with private schools in Brazil and Puerto Rico, I argue that upper-class parents viewed school choice not only in terms of aspirations for their children but as a reflection of therapeutic, personal growth projects and forms of self-cultivation and self-fashioning to which they themselves aspired.
Keywords: 300